A Study of Outdoor Concentrations of Particulate Matter (PM2.5) on Different Floors of a University Building - Norden, Norhanani Aina; Hamzah, Nurhidayah; Akbar, Nor Azliza; Mohd Kamil, Nor Amani Filzah (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Residents at Universiti Tun Hussein Onn (UTHM) buildings complained about dust from nine nearby factories. This study compared PM2.5 levels on different floors of a building to the New Malaysia Ambient Air Quality Guideline (NAAQG). Met One E-Sampler was used to measure PM2.5 and meteorological characteristics at different floor levels. Data was collected daily for 24 hours on each floor, except on public holidays, at two monitoring locations: FKAAB and FSKTM. This study analyzed PM2.5 on different floors and hours. On the ground level of FKAAB and the third floor of FSKTM, the average PM2.5 concentration was 29 µg/m3 and 31 µg/m3, respectively. The 2nd floor FKAAB reveals similar levels as the ground floor, 28 µg/m3. 2nd floor FKAAB was 3rd floor FSKTM. Both levels have the greatest PM2.5 concentration in UTHM air. PM2.5 concentrations were below the NAAQG (35 µg/m3). The greatest PM2.5 concentration was detected at 8:00 p.m. with 39 µg/m3 on the bottom level of FKAAB. The highest PM2.5 concentration on the third floor of FSKTM was 51 µg/m3 at 8:00 a.m. and 11 µg/m3 at 4:00 p.m. Human activity such as nearby industries, buildings, and heavy traffic altered the concentrations. In conclusion, more research is needed to determine which human activities contribute the most to UTHM air pollutants.